Long-term use of oral hygiene products containing stannous and fluoride ions: effect on viable salivary bacteria - Kruse, Anne Brigitte; Schlüter, Nadine Kai; Kortmann, Viktoria Konstanze; Frese, Cornelia; Anderson, Annette; Wittmer, Annette; Hellwig, Elmar; Vach, Kirstin; Al-Ahmad, Ali (Antibiotics, 2021)
The aim of this randomized, controlled clinical trial was to isolate and identify viable microorganisms in the saliva of study participants that continuously used a stannous and fluoride ion (F/Sn)-containing toothpaste and mouth rinse over a period of three years in comparison to a control group that used stannous ion free preparations (noF/Sn) over the same time period. Each group (F/Sn and noF/Sn) included 16 participants that used the respective oral hygiene products over a 36-month period. Stimulated saliva samples were collected at baseline (T0) and after 36 months (T1) from all participants for microbiological examination. The microbial composition of the samples was analyzed using culture technique, matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry, and 16S rDNA Polymerase Chain Reaction (PCR). There were only minor differences between both groups when comparing the absolute values of viable microbiota and bacterial composition. The treatment with F/Sn led to a slight decrease in disease-associated and a slight increase in health-associated bacteria. It was shown that the use of stannous ions had no negative effects on physiological oral microbiota even after prolonged use. In fact, a stabilizing effect of the oral hygiene products containing stannous ions on the health-associated oral microbiota could be expected.
Gesehen am 15.06.2021